Prevalence of aspirin and clopidogrel resistance in neurovascular stenting: a single-center experience - Atasoy, Dilara; Dinç, Hasan; Oğuz, Şükrü; Sönmez, Mehmet (The European Research Journal, 2021)
Objectives: The objective of this study was to determine the frequency of aspirin and clopidogrel resistance of patients undergoing neurovascular stenting procedure in the interventional radiology unit. Methods: The Multiplate® Analyzer (Roche Diagnostics, Germany) test data of 250 patients who underwent carotid or intracranial artery stenting due to atherosclerotic stenosis or treatment of intracranial aneurysms between 2013-2017 in the Interventional Radiology Unit of our hospital were evaluated retrospectively to detect the aspirin and clopidogrel resistance. Aspirin or clopidogrel resistance defined as the higher AUC value than 40U and 46U, respectively. The patients who did not have a result of the Multiplate® test; had anemia, known coagulation disorder or thrombocytopenia were excluded. Results: Among the 172 patients who met the inclusion criteria, 59 (34.3%) were those who had an intracranial stent during aneurysm treatment, and 113 (65.7%) had carotid stenting due to atherosclerotic stenosis. The prevalence of aspirin resistance was 9.4% (16/170) whereas that of clopidogrel resistance was 23.8% (41/172). Among the patients with atherosclerotic stenosis, aspirin resistance accounting for 3.6%, and clopidogrel resistance was 23.0%. Furthermore, the resistance in the patients with stent-assisted coiling for aneurysm treatment was 20.7% for aspirin and 25.4% for clopidogrel. Conclusions: In our study, the prevalence of aspirin resistance was found 9.4% and clopidogrel resistance 23.8% in patients who had neurovascular stenting. The effect of this condition on clinical outcomes in these patients should be investigated by randomized controlled trials.